In vivo synthesis of selenium nanoparticles by Halococcus salifodinae BK18 and their anti‐proliferative properties against HeLa cell line. (25th September 2014) - Srivastava, Pallavee; Braganca, Judith M.; Kowshik, Meenal
<x xml:space="preserve">Abstract</x> Nanoparticles synthesis by bacteria and yeasts has been widely reported, however, synthesis using halophilic archaea is still in a nascent stage. This study aimed at the intracellular synthesis of selenium nanoparticles (SeNPs) by the haloarchaeon Halococcus salifodinae BK18 when grown in the presence of sodium selenite. Crystallographic characterization of SeNPs by X‐ray diffraction, Selected area electron diffraction, and transmission electron microscopy exhibited rod shaped nanoparticles with hexagonal crystal lattice, a crystallite domain size of 28 nm and an aspect ratio (length:diameter) of 13:1. Energy disruptive analysis of X‐ray analysis confirmed the presence of selenium in the nano‐preparation. The nitrate reductase enzyme assay and the inhibitor studies indicated the involvement of NADH‐dependent nitrate reductase in SeNPs synthesis and metal tolerance. The SeNPs exhibited good anti‐proliferative properties against HeLa cell lines while being non‐cytotoxic to normal cell line model HaCat, suggesting the use of these SeNPs as cancer chemotherapeutic agent. This is the first study on selenium nanoparticles synthesis by haloarchaea. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:1480–1487, 2014